2021
DOI: 10.3390/insects12090767
|View full text |Cite
|
Sign up to set email alerts
|

MtDNA Analysis Indicates Human-Induced Temporal Changes of Serbian Honey Bees Diversity

Abstract: Local populations of Apis mellifera are rapidly changing by modern beekeeping through the introduction of nonnative queens, selection and migratory beekeeping. To assess the genetic diversity of contemporary managed honey bees in Serbia, we sequenced mitochondrial tRNAleu-cox2 intergenic region of 241 worker bees from 46 apiaries at eight localities. Nine haplotypes were observed in our samples, with C2d being the most common and widespread. To evaluate genetic diversity patterns, we compared our data with 169… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 59 publications
0
14
1
Order By: Relevance
“…It is important however to note that, in parallel, feral populations are present and numerous in South America and Australia. In Europe, several subspecies are under threat due to loss of genetic diversity as a result of admixture (previously isolated populations interbreeding) (Jensen et al, 2005;Ellis et al, 2018;Espregueira Themudo et al, 2020;Henriques et al, 2021;Tanasković et al, 2021). Additionally and as we will see below, migratory beekeeping, queen trade, breeding and selection for specific traits may ultimately reduce the fitness of managed and wild populations.…”
Section: Status and Threats On Wild-living And Managed Honey Bee Popu...mentioning
confidence: 99%
See 2 more Smart Citations
“…It is important however to note that, in parallel, feral populations are present and numerous in South America and Australia. In Europe, several subspecies are under threat due to loss of genetic diversity as a result of admixture (previously isolated populations interbreeding) (Jensen et al, 2005;Ellis et al, 2018;Espregueira Themudo et al, 2020;Henriques et al, 2021;Tanasković et al, 2021). Additionally and as we will see below, migratory beekeeping, queen trade, breeding and selection for specific traits may ultimately reduce the fitness of managed and wild populations.…”
Section: Status and Threats On Wild-living And Managed Honey Bee Popu...mentioning
confidence: 99%
“…Had the genetic diversity of managed honey bees been increased through admixture before (Harpur et al, 2012;Oldroyd, 2012), the consequent homogenization might ultimately drive the loss of local adaptations (De la Rua et al, 2013). Recent studies showed that, since the 2nd half of the 20th century, the genetic diversity of several European honey bee populations has significantly decreased in their native range (Espregueira Themudo et al, 2020;Tanasković et al, 2021). How can this initiated and speedy loss be stopped?…”
Section: Conserving the Genetic Diversity Of Wild And Managed Honey B...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous analysis showed that of four C lineage subspecies, Serbia harbors two (A. m. macedonica and A. m. carnica) which are clinaly distributed from the northwest (carnica) to the southeast (macedonica) with a hybrid zone between them [23,26,44,45]. Furthermore, nine described mtDNA haplotypes for tRNA leu -cox2 of which two are novel [46] and three distinct ecotypes belonging to specific geographical regions [47] reflect significant genetic variability of A. mellifera in this region. In the past 30 years, the variability of Serbian honey bees has been extensively described on morphological [26,48], etiological [49,50], and genetic levels [26,44,45,47,[51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…Serbia is one of the countries that has embedded in its legislation the preservation of autochthonous species, subspecies, and races, and as per the Law on Animal Breeding from 2009, breeding and keeping of only A. m. carnica are allowed in its territory [55]. Recent work based on the variability of the tRNA leu -cox2 mtDNA region [46] suggests that the composition and distribution of honey bee populations in Serbia has changed over the past decade, invoking the need for further examination of genetic variability on various levels.…”
Section: Introductionmentioning
confidence: 99%